PENENTUAN HARGA POKOK PRODUKSI KOPI BUBUK PADA PT. SENANG ABADI SORONG - Menik Wijayanti; Joice Marantika (SOSCIED, 2020)
In general, companies that are established have a specific purpose. The purpose is the starting point for carrying out all activities within the company. Manufacturing companies are companies whose main business activities are processing raw materials into finished products, then selling the resulting products. One thing that can be done for manufacturing companies in the policy in determining the calculation of the cost of goods manufactured. PT. SENANG ABADI is a manufacturing company, which produces ground coffee. In the production process activities, this company has not implemented and determined the cost of goods manufactured by accounting procedures, in terms of collection and classification of costs not yet collected according to the elements of production costs. Therefore, the company does not know how much the actual cost of production is issued by the company during the production process. The purpose of this research is to find out how to calculate the cost of goods manufactured at PT. SENANG ABADI is it by the cost accounting concept. The method used in this research is a literature study, interview, and observation. In calculating the cost of production, the company has not taken into account all production costs incurred during the production process. In determining factory overhead costs, the company only takes into account the cost of electricity but takes into account all the costs of labor as direct labor. PT. Senang Abadi should collect all production costs according to the elements of production costs incurred during the production process. So that the calculation of the cost of production is correct and provides accurate profit information.